Spectroscopic properties of lead fluoroborate glasses doped with ytterbium - Kassab, LRP; Tatumi, S. H.; Morais, A. S.; Courrol, L. C.; Wetter, N. U.; Salvador, VLR (Optical Soc Amer, 2001)
A new lead fluoroborate glass (PbO-PbF2-B2O3) doped with ytterbium (Yb:PbFB) is presented. Samples with different concentrations of Yb3+ were produced and had their emission cross-sections, fluorescence lifetimes and minimum pump intensities determined. They have high refractive index of 2.2 and a density of 4.4 g/cm(3). For a doping level of 1.153x10(20) ions/cm(3), the fluorescence lifetime, after excitation at 968 nm, is 0.81 ms, which is comparable to Yb:tellurite laser glass. Also, an emission band at 1022 nm is measured with emission cross-section of approximately 1.07x10(-20) cm(2) and fluorescence effective linewidth of 60 nm, which is comparable to Yb:phosphate laser glass. (C) 2001 Optical Society of America.